Neurological mechanisms of mental fatigue in cognitive flexibility in soccer players: an event-related potential study based on N2 components - Gong, Chen; Zhao, Jun; Wang, Yifan; Ding, Xuejian (Frontiers in Neuroscience, 2025)
ObjectivesMental fatigue frequently occurs in team sports characterised by high cognitive demands and can adversely affect athletes’ decision-making and executive functions. This study examines the impact of mental fatigue on cognitive flexibility in soccer players, employing event-related potentials (ERP) to elucidate the underlying neural mechanisms.MethodEighteen football players from the China University Football Association (CUFA) participated in the study. The research utilised the Stroop task to induce mental fatigue and the More-odd switching task to evaluate cognitive flexibility, with measurement indicators comprising accuracy rate (ACC), reaction time (RT), and N2 component amplitude. The experimental design adhered to a repeated measures protocol, incorporating 2 (time: pre-fatigue/post-fatigue) × 2 (task type: conversion/non-conversion) × 4 (electrode positions: Fz, Cz, Pz, F3) factors. Statistical analyses of behavioural data were conducted using non-parametric tests, while ERP data were examined through repeated measures ANOVA.ResultsMental fatigue significantly impaired athletes’ accuracy in the More-odd switching task, evidenced by decreased performance in both conversion and non-conversion conditions (p < 0.05), alongside prolonged reaction times (p < 0.01). Event-related potential (ERP) analysis demonstrated a marked reduction in the amplitudes of the N2 component post-intervention, with notable differences across electrode sites (F = 3.192, p = 0.031). These findings suggest a restriction in cognitive control resources within the frontal and parietal regions.ConclusionThis study illustrates that experimentally induced mental fatigue has a significant detrimental impact on the cognitive performance of football players, leading to slower reaction times and decreased neural electrophysiological indicators (specifically, a reduction in N2 wave amplitude), indicating a decline in conflict monitoring ability. An integrated examination of both behavioural and neurophysiological data indicates that the adverse effects of mental fatigue are likely due to the depletion of general cognitive control resources that rely on the prefrontal cortex, rather than targeting particular cognitive functions. These results offer initial insights into the cognitive and neurological alterations in fatigued athletes. While the study did not explore interventions, the findings lay the groundwork for the development of tailored cognitive training programmes and fatigue management strategies, along with potential evaluation criteria. Notably, the N2 wave amplitude serves as a key metric for assessing cognitive resource levels in football players.